The Effect of Dining Service Quality (DINESERV) on Tourist Satisfaction in The Café Area Muaya Beach Jimbaran, Bali - Ni Putu Lilik Widyayanthi; Ni Ketut Arismayanti; Putu Sucita Yanthy (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Muaya Jimbaran Beach Cafe area Bali is known by tourists as a culinary tourist attraction with a selection of seafood dishes. The café area is highly dependent on domestic and foreign tourists, but the Covid-19 pandemic has resulted in a decrease in the number of tourist visits and there are several negative reviews from tourists related to the quality of services provided. The purpose of this study was to analyze the effect of dining service quality on tourist satisfaction in the area of Muaya Beach Cafe, Jimbaran, Bali Island. This research method uses a quantitative approach with a sample of 115 respondents. Sampling techniques in this study using accidental sampling and data collection through the dissemination of questionnaires, observations, interviews, and literature studies. Data analysis techniques using Structural Equation modeling (SEM) with analysis tools SmartPLS Professional 3.0. The results of this study showed that the dining service quality café in the beach area of Muaya Jimbaran Bali. The results of this study give the implication that we should improve the quality through food quality, service quality, price and atmosphere to achieve optimal tourist satisfaction in the area of Muaya Jimbaran Beach Cafe Bali.